Stretching resilience and adaptive transport systems capacity in South Africa: Imperfect or perfect attempts at closing COVID -19 policy and planning emergent gaps. (September 2022) - Chakwizira, James
Abstract: The COVID-19 pandemic has presented a new wave of health, infrastructure and built environment challenges and opportunities. The COVID-19 pandemic induced environment presents a divide between the "new and old normal" with policy and planning implications for health, transport and general socio-economic growth and development. Multiple and complex nuanced transport matters cascade all geographic scales and pervade all sectors of the economy. The extent to which existing transport systems capacities are resilient, adaptive, and optimized for complete disaster planning, management and sustainability is questioned. This paper critically reviews how the COVID-19 pandemic has stretched the resilience and adaptive transport systems capacities in South Africa. A critical question interrogated is whether on-going policy and planning interventions constitute imperfect or perfect attempts at closing COVID -19 policy and planning emergent gaps. The paper makes use of South Africa as a case study, referencing the Disaster Management Act (No. 57 of 2002) and logical Disaster Management Act: Regulations relating to COVID-19 (Government Notice 318 of 2020), 1 with specific reference to the transport sector lockdown regulations in unravelling policy and planning implications. Drawing from the complex systems adaptive theory (CSAT), sustainability theory (ST), innovation theory (IT), transitions theory (TT), thematic COVID -19 transport planning and policy adaptation, mitigation measures in the South African transportation sector are discussed. Emergent lessons with respect to developing and advancing a new generation of resilient, adaptive, and optimized transport proof infrastructure and services including revising transport and related policies that navigates through various waves and cycles of induced pandemic and shocks is suggested. Highlights: The transport divide between the "new and old normal" planning and policy regimes. COVID-19 transport complexities, challenges, and tensions in policy (re)formulation. Questions whether policy and planning interventions constitute (im)perfect attempts at closing COVID -19 emergent gaps. Emergent lessons for resilient, adaptive, and optimized transport proof COVID -19 infrastructure and services are suggested.